Explaning Existence By IBN AGIBA LHASNY (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Mysticism as a spiritual speculative and desent special and moral experience, based on a sensual strife which lead to the holy truth of god theoricly and practecly; has offerd its special vision of existence.While it has been different thought about explening the existence and its relatation with god.som of it was based on holy books some was based on heathenism or philosophy ,and other some was mix both.In this study ,we are trying to  present an integral moderate picture about the existence and   its explination as the sufi IBN AGIBA lhasny.Has offered  it .who has refused the immanentism either pantheism to explain the existence.he affirmed the duality(GOD-EXISTENCE) to prove to be true the witnessing of god presence harmonizing between   Islamic law and Sufism and the truth of god.